The relationship between running power and running economy in well-trained distance runners - Austin, C. L.; Hokanson, J. F.; McGinnis, P. M.; Patrick, S. (Sports, 2018)
A novel running wearable called the Stryd Summit footpod fastens to a runner`s shoe and estimates running power. The footpod separates power output into two components, Stryd power and form power. The purpose of this study was to measure the correlations between running economy and power and form power at lactate threshold pace. Seventeen well-trained distance runners, 9 male and 8 female, completed a running protocol. Participants ran two four-minute trials: one with a self-selected cadence, and one with a target cadence lowered by 10%. The mean running economy expressed in terms of oxygen cost at self-selected cadence was 201.6 ± 12.8 mL·kg-1·km-1, and at lowered cadence was 204.5 ± 11.5 mL·kg-1·km-1. Ventilation rate and rating of perceived exertion (RPE) were not significantly different between cadence conditions with one-tailed paired t-test analysis (ventilation, p = 0.77, RPE, p = 0.07). Respiratory exchange ratio and caloric unit cost were significantly greater with lower cadence condition (respiratory exchange ratio, p = 0.03, caloric unit cost, p = 0.03). Mean power at self-selected cadence was 4.4 ± 0.5 W·kg-1, and at lowered cadence was 4.4 ± 0.5 W·kg-1. Mean form power at self-selected cadence was 1.1 ± 0.1 W·kg-1, and at lowered cadence was 1.1 ± 0.1 W·kg-1. There were positive, linear correlations between running economy and power (self-selected cadence and lower cadence, r = 0.6; the 90% confidence interval was 0.2 to 0.8); running economy and form power (self-selected cadence and lower cadence r = 0.5; the 90% confidence interval was 0.1 to 0.8). The findings suggest running economy is positively correlated with Stryd`s power and form power measures yet the footpod may not be sufficiently accurate to estimate differences in the running economy of competitive runners.